Implementation of the Waterfall Method in Designing and Building an Income and Cost Management Information System: Case study: Limited Liability Company Adau Kapuas - Arizona, Nanda Diaz; Yulia, Yulia; Adwiya, Rabiatul (Bulletin of Computer Science and Electrical Engineering, 2023)
Adau Kapuas is a company operating in the transportation services sector. In processing income and costs, Adau Kapuas Limited liability companies still use bookkeeping as a data collection medium, such as recording payment and expenses, which are processed starting from recording ticket sales and goods delivery transactions, which process passenger data and goods delivery data. The income obtained from tickets and delivery of goods and the total costs are then entered back into the computer. This proves the difficulty faced by Adau Kapuas, namely having to do work twice daily. This research discusses the application of income and cost processing at Adau Kapuas Pontianak. This application was designed using Netbeans IDE 8.2. It can process admin data, types of goods, types of income, costs, bus classes, destinations, ticket sales transactions, delivery of goods, income transactions, and cost transactions. The reports produced by this application include ticket sales reports, goods delivery reports, income reports, and cost reports. With the income and expense processing application, it is hoped that it can support the performance of Adau Kapuas Pontianak in processing income and expense transactions and presenting reports more easily, quickly, and accurately.